Agroecology Is Affecting Village Chicken Producers' Breeding Objective in Ethiopia. (13th January 2022) - Tilahun, Minyahel; Mitiku, Mosa; Ayalew, Wondossen
Abstract : This study assessed factors that determine village chicken producers' trait preferences in different agroecologies of Ethiopia. Three hundred and eighty village chicken producers were sampled for individual interviews. Data were analyzed using descriptive and inferential statistical techniques. Inbreeding coefficients of chicken populations in the three major agroecologies were estimated. In addition, the multivariate regression model was employed to evaluate the degree to which agroecological difference and socioeconomic and institutional factors impact village chicken producers' trait preferences. Egg and meat production for consumption and income generation were the three major village chicken production functions in the study. Plumage color and weight were ranked first for male and female chicken, respectively. Red plumage color (52.4%) was the primary choice followed by white color (24.5%). Agroecology and livestock holding (TLU) significantly (P < 0.05 ) affected farmers' preference toward economic traits, while land holding significantly (P < 0.05 ) affected reproductive traits. Distance to market significantly (P < 0.05 ) affected farmers' preference toward adaptive traits. The inbreeding coefficient of 0.25, 0.23, and 0.06 was recorded in low, mid, and highland agroecologies, respectively. The agroecological difference is affecting village chicken producers' breeding objective in Ethiopia. A higher inbreeding coefficient was observed in the low and mid agroecologies. Future breed improvement programs should give due consideration to village chicken producers' socioeconomic characteristics and agroecological differences.